This I Believe - Dale, Henry H. (Henry Hallett) (Tufts Archival Research Center, 2006)
Nobel Prize winning President of the Royal Academy, Henry Dale describes his belief in the "supreme value of truth" and the need for science to join forces with religion to help explain both material reality and our immaterial feelings of free will and a moral purpose in life.